Chemistry and immunostimulatory activity of a polysaccharide from Undaria pinnatifida. (June 2019) - Yu, Yongyi; Zhang, Yajun; Hu, Cebin; Zou, Xinyuan; Lin, Yang; Xia, Yangyuan; You, Lijun
Abstract: An immunologically active polysaccharide named as UPP-2 (1035.52 kDa) was isolated from Undaria pinnatifida using traditional water extraction followed by DEAE Sepharose fast flow chromatography. UPP-2 was proven to be a low sulfated polysaccharide with relatively abundant uronic acid (13.08 ± 0.67%). UPP-2 mainly consisted of xylose (64.55%), glucose (23.81%), arabinose (5.90%) and mannose (4.26%), and its main glycosidic linkage types included →2)- α -D-Xylp-(1→, →4)- α -D-Glcp-(1→, α -D-Xylp-(1→ and →2, 4)- β -D-Xylp-(1 → . Results indicated that UPP-2 significantly promoted the proliferation and pinocytic capacity of RAW264.7 cells, and upregulated the mRNA expressions of iNOS, TNF- α, IL-6 and IL-1 β at 100–600 μg/mL with a maximum of 195, 42, 768 and 539 times of those of the negative control, respectively. Moreover, UPP-2 significantly increased the secretions of nitric oxide, TNF- α and IL-6 at 100–600 μg/mL (8.0, 73.1 and 188.7 times compared to those of the negative control, respectively), as well as promoted the production of IL-1 β obviously at 600 μg/mL. Overall, UPP-2 could be served as a potential dietary supplement or functional food based on its immunostimulatory activity. Graphical abstract: Image 1 Highlights: A novel polysaccharide named as UPP-2 was purified from Undaria pinnatifidausing. The composition and structural characteristics of UPP-2 were investigated. UPP-2 upregulate mRNA expressions of iNOS, TNF-α, IL-6 and IL-1β in RAW264.7 cells. UPP-2 could significantly increase the secretions of nitric oxide, TNF-α and IL-6.